Pengontrolan Bahaya Kebakaran Berbasis IOT pada Ruang Server SMFR Balai Monitor Spektrum Frekuensi Radio Kelas II Batam - Eko Setiawan; Nurhatisyah Nurhatisyah; Suwadi Nanra (Penerbit Goodwood, 2022)
Monitoring the security of the SMFR server room is one of the problems at the Batam Class II Radio Frequency Spectrum Monitoring Center, especially against fire hazards. Purpose: To control hazards that can interact with the internet as part of the IoT (Internet of things) so that early detection of fires can be carried out at any time and via a smartphone that displays data from fire sensors, smoke sensors and sensors, while the control measures are activation of alarms, exhausts, openings doors and windows as well as LEDs as fire extinguisher activation indicators so as to minimize equipment damage in the SMFR server room. Methodology: The implementation method used is the design and manufacture of server room miniatures, the design and manufacture of a control system using the Arduino Mega 2560, the design and manufacture of IoT monitoring and control as well as tool testing. Results: From the test results, when the input sensor data, namely fire, temperature and smoke, do not meet these conditions, there will be no fire, all fire handling actions are not active. However, if all the conditions for the input sensor data are met and the threshold value is determined, i.e. there is a smoke fire >37 ppm and a temperature >37? then these conditions will trigger a fire so that all fire handling actions in the form of alarms, exhausts, doors, windows, and LEDs will active. As well as sending fire notifications to Smartphones so that fire events can be detected and handled early. IoT-based testing is carried out using a 4G network, The test results show that Blynk supports capable IoT but depending on the type of real-time connection, the type of network connection used provides varying delay effects. The average delay that 4G produces is 1 to 5 seconds.